2019
DOI: 10.1016/j.system.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Spacing effects on repeated L2 task performance

Abstract: This is a repository copy of Spacing effects on repeated L2 task performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 37 publications
7
47
1
Order By: Relevance
“…Last, authors of future research can simply examine the spacing effects of task repetition on transfer (e.g., AAA [massing] vs. A__A__A [spacing]). To the best of the author's knowledge, only one empirical study has been carried out to systematically investigate the effects of task‐based practice distribution for L2 fluency development (Bui, Ahmadian, & Hunter, 2019). That study's findings indicated that the amount of spacing between repeated tasks can influence some aspects of L2 fluency (i.e., speed and breakdown fluency).…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Last, authors of future research can simply examine the spacing effects of task repetition on transfer (e.g., AAA [massing] vs. A__A__A [spacing]). To the best of the author's knowledge, only one empirical study has been carried out to systematically investigate the effects of task‐based practice distribution for L2 fluency development (Bui, Ahmadian, & Hunter, 2019). That study's findings indicated that the amount of spacing between repeated tasks can influence some aspects of L2 fluency (i.e., speed and breakdown fluency).…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Previous studies have reported that repetition improves oral performance by easing learners' memory recovery of their mental demonstrations that represent previous readings or utterances. In a recent article, Bui, Ahmadian and Hunter (2019) asserted that experience creates complex, eloquent or precise speech functionality. Learners apply cognitive functions to adopt, organise and verbalise information during TR.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, researchers have argued that the spacing between repetitions is of high importance in improving vocabulary retention (Goossens, Camp, Verkoeijen, & Tabbers, 2016). The term spacing is the phenomenon of distributed learning conditions (Bui, Ahmadian, & Hunter, 2019;Rogers, 2017). Moreover, the latest studies have illustrated the importance of intervals during studying which are separated in time in particular vocabulary learning (Namaziandost et al, 2020).…”
Section: Introductionmentioning
confidence: 99%